Pengaruh Pijat Medic Pediatric sebagai Terapi Konstipasi pada Bayi 6-12 Bulan di PMB Handayani Tahunan - Siti Masudah; Indah Risnawati; Atun Wigati (Journal of Midwifery and Health Science of Sultan Agung, 2026)
Constipation in babies is a common condition that can be caused by various factors, including diet, lack of fluid intake, and the introduction of solid foods too early. Baby massage as touch therapy has many positive benefits that can support babies and their development and can be a complementary therapy for babies with constipation. Based on the results of a preliminary study conducted by researchers at the 2024 Annual PMB Handayani inJanuary–August 2024 it was found that 85 respondents experienced constipation. Researchers took 10 respondents, of the 10 respondents were given Medic Pediatric Massage therapy the 8 respondents have reduce constipation. Thus, researchers are interested in conducting research on the Effect of Pediatric Medic Massage as Constipation Therapy in Babies 6-12 Months at the Annual PMB Handayani. The aim of the research is to determine the effect of pediatric medical massage as constipation therapy in babies 6-12 months old at the annual PMB Handayani. Method: The research location was carried out at PMB Handayani Tahunan. The research was carried out using a purposive sampling method, obtaining a sample of 36 respondents according to the inclusion and exclusion criteria. Univariate data analysis using descriptive statistics and bivariate analysis using the SPSS Wilcoxon test. The research results showed that most of the respondents who experienced constipation were female (66.7%), the majority of respondents were 7 months old (30.6%), and the majority were still given soft porridge MPASI, namely 55.6% of babies. Before medical massage was carried out to treat constipation, 36 respondents (100%) all experienced prolonged defecation or more than two days. The results of the Wilcoxon test on the effect of medical massage as constipation therapy on babies aged 6-12 months obtained a p value of 0.0001, this value is less than 0.05, so it can be concluded that there is an effect of medical massage as constipation therapy on babies aged 6-12 months.